Landscape and Ecological Engineering - Landscape and Ecological Engineering (Springer Nature, 2026)
Landscape and Ecological Engineering is a hybrid journal with the aim of protecting and improving the environment in the face of biodiversity loss, desertification, global warming, and other environmental conditions. Journal of the International Consortium of Landscape and Ecological Engineering (ICLEE). Presents original papers, reports, reviews and technical notes on all aspects of ecosystem conservation, restoration, and management. Aims to protect and improve the environment in the face of biodiversity loss. Scope is not limited to purely scientific approaches; welcomes technological and design approaches that provide useful and practical solutions to today's environmental problems. Coverage is relevant to students and researchers at universities and institutes, while its emphasis on the practical application of research will interest all decision makers dealing with landscape planning and management problems.
FI 0.52
Q2
Keywords: Earth; Space & Environmental Sciences; Ecotoxicology & Pollution Science; Ciencias de la contaminación; Ecotoxicología; Acuerdos transformativos; Transformative agreements; Biodiversidad; Calentamiento global; Condiciones ambientales